Health risks of environmental exposure to microplastics - Klaudia Oleksiuk; Karolina Krupa-Kotara; Mateusz Grajek; Agata Wypych-Ślusarska; Joanna Głogowska-Ligus; Jerzy Słowiński (Kazimierz Wielki University, 2022)
Plastics are materials widely used in all sectors. The subject of interest in recent years has become so-called microplastics, whose composition and structure are causing new environmental hazards. The presence and accumulation of microplastics in the environment threaten the ecological balance, the water environment, food sustainability and safety, and ultimately human health. Human exposure to microplastics is primarily through the oral route, so the main source of human exposure to microplastics is diet. Despite many studies focusing on microplastic contamination in seafood, fish, and shellfish, estimating total human exposure to microplastics via the oral route is difficult, due to the lack of research on other foods in this area. The risks to human health from inhaling microplastics remain unclear. According to the WHO, there is no reliable evidence of the harmful effects of microplastic on the human body, but the phenomenon requires further research. Likely health effects of human exposure to microplastic include respiratory and gastrointestinal effects, oxidative stress, and cancer. There is a need to raise public awareness about environmental exposure to microplastics and effective waste management.